A multi-parameter family of three-step eighth-order iterative methods locating a simple root - Geum, Y.H.; Kim, Y.I. (Elsevier, 2010)
A multi-parameter family of three-step eighth-order iterative methods free from second derivatives are proposed in this paper to find a simple root of nonlinear algebraic equations. Convergence analysis as well as numerical experiments confirms the eighth-order convergence and asymptotic error constants. (C) 2009 Elsevier Inc. All rights reserved.